The retrofitting a chevrolet spark into an electric car. - PhD, Professor Abdurazzakov Umidulla Abdurazzakovich; Khushvaktov Sardar Kenja Oghly (Periodica Journal, 2023)
This article provides instructions on how to dismantle the unnecessary equipment for the electric car in the Spark passenger car and install the necessary equipment for the electric car. in addition, the article calculates the selection of an electric engine and electrical equipment with a power suitable for the weight and external dimensions of the Chevrolet Spark car. Economic calculations and indicators for retrofitting a Chevrolet Spark car into an electric car are also covered in the article.
Keywords: electric motor; bLDC; battery